2021
DOI: 10.1108/jeee-04-2021-0165
|View full text |Cite
|
Sign up to set email alerts
|

The role of social entrepreneurship in socio-economic development: a meta-analysis of the nascent field

Abstract: Purpose This study aims to present the first meta-analysis of the research on social entrepreneurship and socio-economic development (SESED). Nation-states, researchers and organizations realized the pivotal role of social entrepreneurship in socio-economic development in the recent two decades. The body of knowledge in this domain witnessed consistent research growth, but it still lacks a critical review to map the scholarly literature and to guide future researchers. Design/methodology/approach This study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 85 publications
(157 reference statements)
1
8
0
Order By: Relevance
“…This research offers a comparative analysis that identifies similarities and commonalities across both commercial and social entrepreneurships. This exploration substantiates the literature and paves a pathway to develop new insights about social entrepreneurship and flourishes with opportunities for additional amplification by researchers, along with practical insinuations for social entrepreneurs to advance systematically and effectively (Ahmad & Bajwa, 2021). Researchers have differently detailed entrepreneurship.…”
Section: Discussionsupporting
confidence: 61%
“…This research offers a comparative analysis that identifies similarities and commonalities across both commercial and social entrepreneurships. This exploration substantiates the literature and paves a pathway to develop new insights about social entrepreneurship and flourishes with opportunities for additional amplification by researchers, along with practical insinuations for social entrepreneurs to advance systematically and effectively (Ahmad & Bajwa, 2021). Researchers have differently detailed entrepreneurship.…”
Section: Discussionsupporting
confidence: 61%
“…This citation analysis is based on the data from Scopus. It is a measure of influence and vitality of research work by calculating how many authors have found their findings helpful and therefore cited them (Ahmad and Bajwa, 2021). The complementary bibliometric analysis is also included, which is generally used to empirically find the most cited articles, famous authors and theme clusters (Campos et al , 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Price [18] pioneered bibliometric analysis, which uses citations to determine the relationship between papers [19]. This technique is widely utilized in various fields, including the social sciences, and is especially prominent in business, management, and economics [20][21]. Qualitative content analysis is a multifaceted or flexible methodology used in the analysis of many social science studies and have been utilized by diverse fields of inquiry [20].…”
Section: Methodsmentioning
confidence: 99%